Enhancing Parental Loyalty through Islamic Relationship Marketing: Empirical Evidence from an Islamic Preschool in Malaysia - Vesma Imamuntiva; Syahrul Amsari (Al-Abshar: Journal of Islamic Education Management, 2026)
Islamic educational institutions increasingly face challenges in maintaining parental loyalty amid growing competition and rising expectations for quality educational services. Conventional relationship marketing often emphasizes customer satisfaction but pays limited attention to ethical and spiritual values that are central to Islamic education. This study aims to explore the implementation of Islamic Relationship Marketing (IRM) in enhancing parental loyalty at Tadika Mutiara Qysara, Kedah, Malaysia. A descriptive qualitative approach was employed, with data collected through participatory observation, semi-structured interviews with teachers, administrators, and parents, as well as documentation analysis. The findings reveal that the integration of Islamic values, including siddiq (honesty), amanah (trustworthiness), tabligh (transparent communication), fathonah (professionalism), justice, and empathy, plays a significant role in strengthening parental trust, satisfaction, active engagement, emotional attachment, and long-term loyalty. These values foster strong alignment between institutional practices and parental expectations, creating sustainable relationships based on mutual trust and shared Islamic principles. The study contributes to the literature by demonstrating that Islamic Relationship Marketing extends beyond a marketing strategy to become an ethical framework for stakeholder relationship management, while offering practical guidance for Islamic early childhood education institutions seeking to enhance parental loyalty through value-based service excellence and sustainable partnership practices.